Emotional Creativity Improves Posttraumatic Growth and Mental Health During the COVID-19 Pandemic - Zhai, Hong-Kun; Li, Qiang; Hu, Yue-Xin; Cui, Yu-Xin; Wei, Xiao-Wei; Zhou, Xiang (Frontiers in Psychology, 2021)
Emotional creativity refers to a set of cognitive abilities and personality traits related to the originality of emotional experience and expression. Previous studies have found that emotional creativity can positively predict post-traumatic growth and mental health. The outbreak of COVID-19 has posed great challenges to people’s daily lives and their mental health status. Therefore, this study aims to address the following two questions: whether emotional creativity can improve post-traumatic growth and mental health during the COVID-19 pandemic and how it works. To do this, a multiple mediation model has been proposed, which supposes that emotional creativity is associated with post-traumatic growth and mental health through perceived social support and regulatory emotional self-efficacy. The study involved 423 participants from multiple regions with different COVID-19 involvement levels. Participants were asked to complete a questionnaire with six parts, which included Emotional Creativity Inventory (ECI), Regulatory Emotional Self-Efficacy Scale (RES), Stress-Related Growth Scale-Short Form (SRGS-SF), Multidimensional Scale of Perceived Social Support scale (MSPSS), Brief Symptom Inventory-18 scale (BSI-18), and COVID-19 related life events questionnaire. Path analysis used to examine the mediation model indicated that under the control of COVID-19 related life events and age, perceived social support mediated a positive association between emotional creativity and post-traumatic growth as well as a negative association between emotional creativity and all mental health problems, including somatization, depression, and anxiety. Regulatory emotional self-efficacy mediates the association between emotional creativity and post-traumatic growth, emotional creativity and anxiety, and emotional creativity and depression. The results suggest that emotional creativity plays an important role in coping with stressful events related to COVID-19. Furthermore, these results might provide a better understanding of the possible paths through which emotional creativity is related to psychological outcomes, such as mental health and post-traumatic growth.